SANKSI PIDANA KEPADA ORANG TUA YANG MELALAIKAN TANGGUNG JAWAB BERDASARKAN UNDANG-UNDANG NARKOTIKA DAN PERLINDUNGAN ANAK - Rumahorbo, Erika Magdalena (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
This study aims to analysing the comparison between the Narcotics Law and the Child Protection Law regarding sanctions against parents who do not fulfil their obligations. This research uses Normative Legal research methods using primary legal materials and secondary legal materials. Primary legal materials, legal materials that are binding in the form of applicable legislation, and secondary legal materials, secondary legal materials are legal materials obtained from law books, legal journals, and scientific articles on law related to the application of sanctions against parents who do not fulfil their obligations in protecting their children. Data collection is carried out using literature studies by searching, exploring collecting, and analysing the necessary data. In addition, this study will invite writers and readers to critically evaluate the validity and reliability of the project or study as a whole from this research which aims to analyse the comparison between the Narcotics Law (UU Narkotika) and the Child Protection Law regarding sanctions against parents who do not fulfil their obligations. The analysis becomes a juridical consideration with a philosophical and conceptual approach. The results of the research will find a comparison between the Narcotics Law and the Child Protection Law regarding sanctions against parents who do not fulfil their obligations. This paper is different from other studies, where this research will focus on examining the comparison between the Narcotics Law and the Child Protection Law regarding the application of sanctions to parents who do not fulfil their obligations.